Southern Hemisphere strong polar mesoscale cyclones in high-resolution datasets - Alexandre Pezza; Katherine Sadler; Petteri Uotila; Timo Vihma; Michel D. S. Mesquita; Phil Reid (Climate Dynamics, 2016)

Significant extra‐tropical anomalies in the lead up to the Black Saturday fires - Sonya L. Fiddes; Alexandre B. Pezza; James Renwick (International Journal of Climatology, 2016)
Black Saturday ( BS ), 7 February 2009, is recognized as Australia's most severe bushfire event on record. The meteorology that day, although extreme, was typical of southeast Australian bushfire events, characterized by gusty northerly winds before a cool change brought strong southerly winds and a dramatic temperature drop. This study investigates a range of extra‐tropical atmospheric (pressure, temperatures) and oceanic temperature anomalies that occurred on or leading up to BS . Results show several parameters were within the top 5% or were record breaking for the satellite era. Of particular note are the anomalies that occurred over the Antarctic region, having the strongest signal and appearing in unison with the pre‐ BS heatwave. We suggest that a combination of a warm polar ocean and an enhanced mid‐latitude thermal contrast in the Indian Ocean aided in triggering sub‐polar blocking and an intense cyclone, which brought the catastrophic cold front on BS .

Heat stress during the Black Saturday event in Melbourne, Australia - Stephanie J. Jacobs; Timo Vihma; Alexandre B. Pezza (International Journal of Biometeorology, 2015)

Current and future climate variability associated with wintertime precipitation in alpine Australia - Sonya Louise Fiddes; Alexandre Bernardes Pezza (Climate Dynamics, 2015)

Large scale and sub-regional connections in the lead up to summer heat wave and extreme rainfall events in eastern Australia - Ghyslaine Boschat; Alexandre Pezza; Ian Simmonds; Sarah Perkins; Tim Cowan; Ariaan Purich (Climate Dynamics, 2015)

Synoptic climatology of extreme precipitation in alpine Australia - Sonya Louise Fiddes; Alexandre Bernardes Pezza; Vaughan Barras (International Journal of Climatology, 2015)
Extreme precipitation over the eastern Australia can be significantly enhanced by topographic interaction with the westerly flow. These extreme events can cause severe flooding, damage and disruption to human activities, yet in some areas they are also an invaluable source of water and snow. In this study, we use rain gauge and snowfall accumulation data to investigate connections between extreme rain and snow in alpine Australia and the large‐scale climate. These data have been divided into three geographical locations: the west of the mountains, the ridgeline and the east of the mountains in order to explore the nature of precipitation in each region. The results confirm previous synoptic patterns found earlier in the literature for the western slopes (namely embedded and cutoff lows), and add new insights into the different processes conducive to extreme precipitation on the eastern side of the ranges, which we find to be mostly associated with a blocking structure connected to polar latitudes. Interestingly, our analyses suggests that while a La Niña pattern accompanied by enhanced meridional sea surface temperature ( SST ) gradients over mid‐latitudes is associated with extreme events in the western and high regions, the extreme precipitation composites for the eastern region are associated with a SST pattern that resembles the predominant signal associated with global warming in the Australian region. We hypothesize that while the western and high regions rely on SST gradients, which enhance the westerly jet, the extreme events over the eastern side rely on blocking patterns (anomalous easterlies), which are at least partially responding to the global SST warming with the respective shift of the westerlies to the south. These results help explain why the precipitation over the western side of the Alps is declining more rapidly than the total precipitation observed on the eastern side.

A new ‘bio-comfort’ perspective for Melbourne based on heat stress, air pollution and pollen - Stephanie J. Jacobs; Alexandre B. Pezza; Vaughan Barras; John Bye (International Journal of Biometeorology, 2014)

Large scale features and energetics of the hybrid subtropical low ‘Duck’ over the Tasman Sea - Alexandre Bernardes Pezza; Luke Andrew Garde; José Augusto Paixão Veiga; Ian Simmonds (Climate Dynamics, 2014)

Climate links and recent extremes in antarctic sea ice, high-latitude cyclones, Southern Annular Mode and ENSO - Alexandre Bernardes Pezza; Harun A. Rashid; Ian Simmonds (Climate Dynamics, 2012)

Severe heat waves in Southern Australia: synoptic climatology and large scale connections - Alexandre Bernardes Pezza; Peter van Rensch; Wenju Cai (Climate Dynamics, 2012)

On the causes of variability in amounts of airborne grass pollen in Melbourne, Australia - Julian de Morton; John Bye; Alexandre Pezza; Edward Newbigin (International Journal of Biometeorology, 2011)

Climate perspective on the large‐scale circulation associated with the transition of the first South Atlantic hurricane - Alexandre Bernardes Pezza; Ian Simmonds; Augusto Jose Pereira Filho (International Journal of Climatology, 2009)
The landfall of Cyclone Catarina on the Brazilian coast in March 2004 became known as the first documented hurricane in the South Atlantic Ocean, promoting a new view on how large‐scale features can contribute to tropical transition. The aim of this paper is to put the large‐scale circulation associated with Catarina's transition in climate perspective. This is discussed in the light of a robust pattern of spatial correlations between thermodynamic and dynamic variables of importance for hurricane formation. A discussion on how transition mechanisms respond to the present‐day circulation is presented. These associations help in understanding why Catarina was formed in a region previously thought to be hurricane‐free. Catarina developed over a large‐scale area of thermodynamically favourable air/sea temperature contrast. This aspect explains the paradox that such a rare system developed when the sea surface temperature was slightly below average. But, although thermodynamics played an important role, it is apparent that Catarina would not have formed without the key dynamic interplay triggered by a high latitude blocking. The blocking was associated with an extreme positive phase of the Southern Annular Mode (SAM) both hemispherically and locally, and the nearby area where Catarina developed is found to be more cyclonic during the positive phase of the SAM. A conceptual model is developed and a ‘South Atlantic index’ is introduced as a useful diagnostic of potential conditions leading to tropical transition in the area, where large‐scale indices indicate trends towards more favourable atmospheric conditions for tropical cyclone formation. Copyright © 2008 Royal Meteorological Society

Southern hemisphere cyclones and anticyclones: recent trends and links with decadal variability in the Pacific Ocean - Alexandre Bernardes Pezza; Ian Simmonds; James A. Renwick (International Journal of Climatology, 2007)
The aim of this paper is to study the association between the extratropical Southern Hemisphere and the decadal variability in the Pacific Ocean (PO). We discuss a pattern of coherent large‐scale anomalies and trends in cyclone and anticyclone behaviour in light of the climate variability in the PO over the ERA40 reanalysis period (1957–2002). The two representative PO indices are the Pacific Decadal and Interdecadal Oscillations (PDO and IPO), and here the PDO is chosen owing to it being less associated with the southern oscillation index (SOI). Composites of the indicators of the density and intensity of cyclones/anticyclones given by an automatic tracking scheme were calculated for the years when the PDOI was more than one standard deviation above or below its mean. Although the ERA40 is not free from noise and assimilation changes, the results show a large‐scale feature, which seems to be robust and agrees with earlier studies using different data sets. The sea‐level pressure shows a strong annular structure related to the PDO, which is not seen for the SOI, with lower pressure around Antarctica during the positive phase and vice versa. More intense (and fewer) cyclones and anticyclones were observed during the positive PDO. This is less consistent for the SOI, particularly during the summer when a different PDO/SOI pattern arises at high latitudes. The trends project a pattern coincident with the positive PDO phase and seem to be linked with the main climate shift in the late seventies. Trends observed over the Tasman Sea are consistent with declining winter rainfall over southeastern Australia. Most patterns are statistically significant and seem robust, but random changes in ENSO may play a part, to a certain degree, in modulating the results, and a physical mechanism of causality has not been demonstrated. Although global warming and related changes in the Southern Annular Mode (SAM) may also help explain the observed behaviour, the large‐scale response presented here provides a new insight and would be of considerable interest for further modelling studies. Copyright © 2007 Royal Meteorological Society

Dynamical conditions and synoptic tracks associated with different types of cold surge over tropical South America - Alexandre Bernardes Pezza; Trcio Ambrizzi (International Journal of Climatology, 2005)